God's stewards: A global overview of Christian-influenced mutual fund providers - Joel Diener; André Habisch (Journal of Risk and Financial Management, 2022)
Despite a large amount of assets under management and a strong influence on the sustainable investment movement, very little is known about what ethical investing looks like from a Christian perspective. We therefore analyzed the ethical investment policies of a unique dataset of Christian-influenced mutual fund providers using a structured-thematic content analysis. In detail, we looked at investment screens, investment techniques, and the public presentation of non-financial investment objectives. We note that, by and large, there is no 'Christian investing' in the sense of an ethical investment policy that most fund providers have similarly implemented. The proposed explanation for the diversity is that the policies are determined by differing approaches to interpreting biblical texts and by divergent social and political influence factors. However, we have detected a unifying element among most Christians-influenced mutual fund providers: the intention to positively influence their portfolio companies' sustainability indicators.
Keywords: 650; socially responsible investments; SRI; Christian finance; faith-based investing; religion; sustainable investing; thematic content analysis